2021
DOI: 10.1158/0008-5472.can-20-1847
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ACSS2 with a Transition-State Mimetic Inhibits Triple-Negative Breast Cancer Growth

Abstract: Acetyl-CoA is a vitally important and versatile metabolite used for many cellular processes including fatty acid synthesis, ATP production, and protein acetylation. Recent studies have shown that cancer cells upregulate acetyl-CoA synthetase 2 (ACSS2), an enzyme that converts acetate to acetyl-CoA, in response to stresses such as low nutrient availability and hypoxia. Stressed cancer cells use ACSS2 as a means to exploit acetate as an alternative nutrient source. Genetic depletion of ACSS2 in tumors inhibits t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 63 publications
0
60
0
Order By: Relevance
“…152 ) is also induced by hypoxia and low serum cell culture media and maintains cancer cell growth under stress. Inhibition of ACSS2 by inducible shRNAs 152 or CRISPR knockout 153,154 suppressed in vivo tumorigenesis. These studies collectively indicate that ACSS2 inhibition could have beneficial antitumour effects.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…152 ) is also induced by hypoxia and low serum cell culture media and maintains cancer cell growth under stress. Inhibition of ACSS2 by inducible shRNAs 152 or CRISPR knockout 153,154 suppressed in vivo tumorigenesis. These studies collectively indicate that ACSS2 inhibition could have beneficial antitumour effects.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…As such, ACSS2 inhibitors are being developed 155 (patents WO/2019/097515, WO/2015/175845 and WO/2020/252407) and await testing in tumour models. A predicted transition-state mimetic inhibitor, VY-3-135, was recently documented to have nanomolar biological activity in vitro and has efficacy in xenograft mouse models with high ACSS2 expression but not in those with low expression 153 . Further, VY-3-135 inhibits the labelling of palmitate by D 3 -acetate, providing evidence for in vivo target engagement.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…Nonetheless, a study on the relationship between ACSS2 and cancer has shown that ACSS2 -mediated histone acetylation plays an important role in maintaining cell homeostasis and tumor development, providing a clearer path for the research of ACSS2 ( 84 ). It is also a new idea to explore the therapy of ccRCC and other cancers that target this gene ( 85 , 86 ). Based on the above study on the application value of ACLY and ACSS2 in cancer treatment, we believe that it is highly practical to develop new treatment methods based on these two genes.…”
Section: Abnormal Metabolism Of Fatty Acids and Cholesterolmentioning
confidence: 99%
“…Recently, Miller et al reported that this inhibitor inhibited ACSS2 at less than 50% at the highest drug concentrations, suggesting that it is not a particularly effective inhibitor of ACS. 34 Thus, small differences in affinity between the two enzymes for the inhibitor may be amplified. Since ACSS2 does not appear essential in mammals, 4 , 5 high specificity for fungal enzymes, however, is not likely to be as important as potent on-target activity in the development of antifungal ACS inhibitors.…”
Section: Resultsmentioning
confidence: 99%